Electrochemotherapy with bleomycin is effective in BRAF mutated melanoma cells and interacts with BRAF inhibitors - Dolinšek, Tanja (Radiology and oncology (Ljubljana), 2016)
The aim of the study was to explore the effectiveness of electrochemotherapy (ECT) during the treatment of melanoma patients with BRAF inhibitors. Its effectiveness was tested on BRAF mutated and non-mutated melanoma cells in vitro and in combination with BRAF inhibitors. Materials and methods. ECT with bleomycin was performed on two human melanoma cell lines, with (SK-MEL-28) or without (CHL-1) BRAF V600E mutation. Cell survival was determined using clonogenic assay to determine the effectiveness of ECT in melanoma cells of different mutation status. Furthermore, the effectiveness of ECT in concomitant treatment with BRAF inhibitor vemurafenib was also determined in BRAF mutated cells SK-MEL-28 with clonogenic assay. Results. The survival of BRAF V600E mutated melanoma cells was even lower than non-mutated cells, indicating that ECT is effective regardless of the mutational status of melanoma cells. Furthermore, the synergistic interaction between vemurafenib and ECT with bleomycin was demonstrated in the BRAF V600E mutated melanoma cells. Conclusions. The effectiveness of ECT in BRAF mutated melanoma cells as well as potentiation of its effectiveness during the treatment with vemurafenib in vitro implies on clinical applicability of ECT in melanoma patients with BRAF mutation and/or during the treatment with BRAF inhibitors.
Keywords: BRAF inhibitors; electrochemotherapy; elektrokemoterapija; melanom; melanoma; vemurafenib; zaviralci BRAF